EFFECT OF PLYOMETRICS EXERCISES ON CARDIO-VASCULAR ENDURANCE AND PLAYING ABILITY OF CRICKET PLAYERS - Sakure, Girish M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Plyometrics, also known as jump training or explosive training, is a type of exercise that involves rapid, high intensity movements that aim to improve muscular power, speed and reactivity.After the statistical Analysis Pre-test and Post-test of control group was not significant, in Cardio-vascular Endurance (t = 0.120), Off Side Batting Ability (t = 0.807), Defend Batting Ability (t = 0.784) and Length Bowling Ability (t = 0.464), Full Length Bowling Ability (t = 0.354), Fielding Ability (t = 0.209) and Overall playing Ability (t = 0.738), because these t-values are less than the tabulated t-value of 2.144 at 0.05 level of confidence of 14 degree of freedom. After the statistical Analysis Pre-test and Post-test of Experimental group was not significant, in Cardio-vascular Endurance (t = 2.172), Off Side Batting Ability (t = 4.299), Defend Batting Ability (t = 3.930) and Length Bowling Ability (t = 3.371), Full Length Bowling Ability (t = 2.567), Fielding Ability (t = 2.347) and Overall playing Ability (t = 7.407), because these t-values are less than the tabulated t-value of 2.144 at 0.05 level of confidence of 14 degree of freedom.